2010
DOI: 10.1055/s-0030-1265217
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Parameters and Nonalcoholic Fatty Liver Disease in Hypopituitary Men

Abstract: Patients with hypopituitarism have the feature of metabolic syndrome, including central obesity, insulin resistance, and dyslipidemia. Because metabolic syndrome, including insulin resistance, is the main pathogenesis of the development of nonalcoholic fatty liver disease (NAFLD), we considered that patients diagnosed with hypopituitarism have an increased risk of developing NAFLD. We compared control subjects and hypopituitary men in metabolic parameters and the frequency of fatty liver on abdominal ultrasono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 19 publications
8
43
0
8
Order By: Relevance
“…Ichikawa et al [8] reported that in patients with adult onset anterior lobe pituitary hormone deficiency (with or without GH deficiency), NAFLD was more frequently observed in patients with GH deficiency. Decreased GH levels were also associated with the severity of hepatic steatosis in other studies [3], [9]. Furthermore, hypothalamic/pituitary dysfunction may be accompanied by progressive NAFLD and excessive weight gain, impaired glucose tolerance, and dyslipidemia [10].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Ichikawa et al [8] reported that in patients with adult onset anterior lobe pituitary hormone deficiency (with or without GH deficiency), NAFLD was more frequently observed in patients with GH deficiency. Decreased GH levels were also associated with the severity of hepatic steatosis in other studies [3], [9]. Furthermore, hypothalamic/pituitary dysfunction may be accompanied by progressive NAFLD and excessive weight gain, impaired glucose tolerance, and dyslipidemia [10].…”
Section: Introductionmentioning
confidence: 68%
“…Low GH secretion from the pituitary is associated with increased visceral body fat and other features of the metabolic syndrome. For example, in a previous study, patients with GH deficiency had significance higher body mass index (BMI) and waist circumference, and elevated serum total cholesterol, low-density lipoprotein cholesterol and triglycerides than the controls [3]. Adult patients with GH deficiency also had a higher prevalence of the metabolic syndrome than the controls [4], [5].…”
Section: Introductionmentioning
confidence: 93%
“…In another case of adult hypopituitary patients with GHD accompanied by nonalcoholic steatohepatitis (NASH) and hyperlipidemia, we reported that GH replacement therapy drastically reversed NASH (6). Moreover, the severity of fatty liver was shown to be related to hypopituitary patients' GH levels (7). Interestingly, in the non-GH-deficient population, GH, insulin-like growth factor 1 (IGF1), and IGF-binding protein 3 were associated with hepatic fibrosis and steatosis in NAFLD (8), suggesting that the GH-IGF1 axis may play an important role in the liver in the physiological condition.…”
Section: Introductionmentioning
confidence: 92%
“…[49][50][51][52][53][54][55][56][57][58][59][60] In addition to poor QoL, both GHD and hypogonadism can contribute to decreased lean body mass, increased fat mass (in particular, visceral fat), and poor exercise capacity that further contribute to poor QoL, obesity, and MetS, increasing cardiovascular disease (CVD) risk. 51,54,57,[61][62][63][64][65][66][67][68][69][70] Studies have shown that MetS is associated with, and predicts the development of, low serum testosterone levels in men. 62,64,65,71 Five of 6 subjects with hypogonadism had MetS and obesity.…”
Section: Previous Studies On Postconcussive Hypopituitarismmentioning
confidence: 99%